FAST TRACK TO SUCCESS PROJECT MANAGEMENT - Derry Simon; Harper-Smith Patrick (Prentice Hall, 2009)
AWARENESS BUSINESS FAST TRACK CAREER FAST TRACK DIRECTOR'S TOOLKIT
AWARENESS BUSINESS FAST TRACK CAREER FAST TRACK DIRECTOR'S TOOLKIT